Students’ Perception: Assessing English Competence in TOEFL As a Standardized English Language Proficiency Test in Indonesian’s Higher Education - Subkhi Dwi Raharjo (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2020)
This study aimed to know the perception of Indonesian students in standardized English proficiency in TOEFL. The research design of this study employed descriptive research. Twenty-seven students from several degrees in university level were selected randomly as the participants. To examine students’ perception, the researcher employed Google Form as an instrument to collect data, and the researcher also employed an interview section as supporting data. In collecting data, the researcher attached nine questions in Google form. Therefore, the questionnaires were analyzed to identify the perception of students in TOEFL as a standardized English Language Proficiency test. In methodology, the researcher employed mix method to investigate in this study, and the questioners distributed randomly by using WhatsApp. Regarding findings in this study, the conclusion revealed that TOEFL as a standardized proficiency test still could be as a benchmark to measure English proficiency in certain kinds such as TOEFL ITP. In addition, the other assessments could be possible as an instrument to measure English proficiency such as portfolio, peer assessment and many more.